Do Women Directors Impact the Risk and Return of Indian Banks?. (January 2021) - Shukla, Ankur; Sivasankaran, Narayanasamy; Singh, Prakash; Kanagaraj, Ayyaluswamy; Chakraborty, Shibashish
The purpose of the paper is to investigate whether women directors impact the risk and return of Indian banks. This study employs panel data models for a sample of 29 Indian banks that form part of the National Stock Exchange 500 index for the period 2009–2016. This paper concludes that women directors influence the accounting returns (measured through Return on Assets) of Indian banks. However, it was found that women directors did not affect the risks (measured through Equity Beta and gross NPA to Total Assets) of the sample banks. This paper contributes to the literature and practitioners in several ways. To the best of the knowledge of the authors, no study has examined the impact of women directors on the risk and return of banks operating in India. Hence, the findings of this article have substantial implications both to academia and practitioners.